30-Day Outcomes of Trans-Carotid Artery Revascularization with Proximal Protection Through ICA Flow Reversal in Neurosurgical Practice. (16th November 2020) - Cord, Branden J; Santarosa, Corrado; Sujijantarat, Nanthiya; Koo, Andrew B; Elsamadicy, Aladine A; Sheth, Kevin; Falcone, Guido; Sansing, Lauren; Schindler, Joseph; Petersen, Nils; Matouk, Charles C
Abstract: INTRODUCTION: Traditional surgical interventions for atheroscleroitc carotid disease include carotid endarterectomy (CEA) and trans-femoral carotid artery stenting (TF-CAS). More recently, transcarotid revascularization (TCAR) has become a competitive option. The TCAR procedure employs an extracorporeal shunt with in-line embolic filter conecting the common carotid artery and femoral vein, establishing flow reversal across the atherosclerotic lesion as a means of proximal protection during angioplasty and stenting. Like TF-CAS, TCAR is reserved for high-risk patients. However, TCAR has theoretical advantages: 1. Protection is established prior to crossing the lesion; 2. Potentially dangerous arch catheter manipulations are bypassed by direct introduction of the catheter into the common carotid artery. In ROADSTER, a single-arm prospective clinical trial, TCAR had a low 1.4% periprocedural stroke rate. With these exciting results, TCAR has growing popularity with most procedures currently performed by vascular surgeons. METHODS: A prospective registry of all carotid revascularizations including CEA, TF-CAS, and TCAR performed by four neurosurgeons at a single hospital were reviewed for TCAR procedures since its introduction. For the TCAR cohort demographic, medical comorbidities, procedural characteristics, in-hospital and, and 30-day outcomes were assessed and reported. RESULTS: Over a 2.5-year period, 163 carotid interventions were performed. The TCAR procedure was attempted in 71 cases (43.6%) and successfully completed in 69 (97.2%) with failures due to a low bifurcation and cannulation of the ICA in one case, and too steep an angle of approach with resultant inability to advance the microsheath in a second case. The TCAR patient population was aged, mostly symptomatic (88.7%), high-risk, surgical patients with high rates of medical comorbidities. In-hospital ipsilateral stroke rate was 2.8% (n = 2), myocardial infarction 2.8% (n = 2), mortality 0% (n = 0), and 0% (n = 0) cranial nerve injuries. Both strokes occurred intra-procedurally in symptomatic patients. No additional events occurred in the perioperative 30-day period. One additional patient suffered from hypoperfusion-induced, transient bilateral hearing loss. CONCLUSION: In a large neurosurgical series, TCAR with proximal protection through ICA flow reversal has a high rate of technical success, and low rates of periprocedural stroke, myocardial infarction, and death. This is in keeping with previously published studies.